Ceramic complex of the Bulandy-2 Temple: morphology, technical and technological analysis - Utubayev Жанболат; Suyundikova Макпал; Kaliyeva Жанаргүл (Turkic Studies Journal, 2025)
This paper presents the results of an analysis of ceramics from Bulandy-2, one of Central Asia’s earliest domed structures. The site was first excavated by the Khorezm Archaeological Expedition between 1957 and 1960. The Bulandy-2 Temple has a circular shape with a diameter of 16 m and a height of 4.5 m. The entrance is located on the northern side of the structure. The presence of a wooden stretcher and a coffin during the excavations suggests that the temple was used for burial purposes. It also points out that the site may have been employed for rituals associated with funerary practices. Researchers comparing the Bulandy-2 Temple with Central Asian cultic monuments in Bactria, Margiana, and Khorezm associate its architectural features, particularly its circular base, the cult of fire and abundance, that is characteristic of the Zoroastrian nomadic traditions of Central Asia. Moreover, similar dome-shaped structures have been found across the Eurasian steppe. The present study draws upon a range of ceramic collections from the Bulandy-2 complex, which are currently housed in the collection of the State Museum of Oriental Art in Moscow. The primary objective of this paper is to introduce the morphological, technical and technological characteristics of Bulandy-2 ceramics into scholarly discourse. Morphological analysis of the pottery indicates the presence of domestic and, to some extent, kitchenware. Further technical and technological analysis of the material reveals that the vessels were wheel-thrown using a mixture of dry clay, chamotte, organic matter and gypsum. The primary artificial organic additives in the moulding mass of this ceramic were dry grass and crushed straw. Large Bulandy-2 vessels were constructed using the coil-building technique. The vessels feature a rich red and brown engobe, along with and various geometric designs on their bases and rims. Researchers suggest that the markings on the ceramics may represent the potter’s personal signature, clients’ requests, indications of private ownership, reflections of social inequality. The conducted research on the site, as well as the morphological and technological- technical analysis of the ceramics, made it possible to date the Bulandy-2 Temple to the 4th-2nd centuries.